Hospital pedagogy and its inclusive view - Rodrigues , Janine Marta Coelho; de Moura, Myrella Gomes (Seven Editora, 2024)
The discussion about Hospital Pedagogy has been growing in recent years, in view of its visible importance in this alternative learning environment. Thus, this article aims to reflect on the training of the pedagogue to work in the hospital context, considering a little of the history and the Brazilian context, within the current inclusive educational paradigm. With this understanding, it sought in the qualitative research, a bibliographic review on the subject, added to a case study illustrated from an experience with Hospital Pedagogy carried out at the Lauro Wanderley University Hospital, at the Federal University of Paraíba (UFPB). The results showed that, in fact, the university extension project "Psychopedagogical Care for Hospitalized Children and Adolescents: Alternative Work for the Pedagogue" is characterized as an important space for the training of the pedagogue, within an inclusive vision of education. And, although it is not officially part of the internship field for Pedagogy students, it has been fulfilling this function through university extension. DOI:https://doi.org/10.56238/sevened2024.018-069